Adenomatous Hyperplasia of the Gallbladder in the Setting of Mirizzi Syndrome, Mimicking Adenocarcinoma of the Gallbladder - Odongo, Charles Newton; Dreque, Carlos Cabrera; Bongomin, Felix; Oyania, Felix; Situma, Martin; Atwine, Raymond (International Medical Case Reports Journal, 2021)
Background: Adenomatous hyperplasia (AH) is an uncommon benign lesion of the gallbladder (GB), predominantly seen in men. AH is commonly confused with malignant GB neoplasms in the setting of chronic cholecystitis and gallstones. There is a scarcity of published literature on AH, suggesting its rarity and the need for this case report. Case Presentation: A 24-year-old woman from Western Uganda presented with signs and symptoms consistent with extrahepatic biliary obstruction. Trans-abdominal ultrasound scan revealed cholecystomegaly (13.9 cm by 4.29 cm), thickened GB wall at 5.2 mm, with a poorly defined hypoechoic polypoid solid mass involving the fundal body of the GB. Explorative laparotomy with cholecystectomy and lymph node sampling was performed. Histopathological examination was consistent with adenomatous hyperplasia of the GB. The symptoms and laboratory values improved on follow-up in the clinic after laparotomy. Conclusion: Adenomatous hyperplasia may be misdiagnosed as a malignant GB neoplasm, especially in the setting of chronic cholecystitis and gallstones. If a correct histopathological diagnosis is made, no further diagnostic work-up is necessary following surgical interventions
Keywords: Adenomatous; Hyperplasia; Gallbladder; Mirizzi syndrome